2002
DOI: 10.1002/cpp.338
|View full text |Cite
|
Sign up to set email alerts
|

Parenting style and obsessive‐compulsive symptoms and personality traits in a student sample

Abstract: There is widespread acceptance of the idea that aspects of parenting such as overprotectiveness and perfectionism contribute to the pathogenesis of obsessive-compulsive disorder (OCD). Less resolved is whether the important dimensions of parenting are overprotectiveness, lack of acceptance, authoritarian style, discouragement of risk-taking, and/or induction of guilt. It is also unclear whether different parenting characteristics are associated with the development of symptoms of OCD, compared to the traits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Similarly, it has been suggested that individuals with OCD may be disturbed by their low sense of control over events that are important to them (Bolton, 1996;Franzblau, Kanadanian, & Rettig, 1995;Frost et al, 1993) or the perceived loss of control over their own behavior (Carr, 1974). Thus, objectively-irrational compulsive behaviors may help to restore feelings of control in threatening situations, when individuals feel that no other avenue for Control-Related Beliefs and OCD 15 control exists (Aycicegi, Harris, & Dinn, 2002;Bolton, 1996;Frost et al, 1993;McFall & Wollersheim, 1979). Consistent with this proposition, empirical research has consistently linked superstitious and magical beliefs to OC symptoms; the strongest relationships demonstrated with compulsive checking (Bolton et al, 2002;Emmelkamp & Aardema, 1999;Frost et al, 1993;Rosen & Tallis, 1995;Roth & Baribeau, 2000;cf.…”
Section: Control-related Beliefs and Ocd 14mentioning
confidence: 99%
“…Similarly, it has been suggested that individuals with OCD may be disturbed by their low sense of control over events that are important to them (Bolton, 1996;Franzblau, Kanadanian, & Rettig, 1995;Frost et al, 1993) or the perceived loss of control over their own behavior (Carr, 1974). Thus, objectively-irrational compulsive behaviors may help to restore feelings of control in threatening situations, when individuals feel that no other avenue for Control-Related Beliefs and OCD 15 control exists (Aycicegi, Harris, & Dinn, 2002;Bolton, 1996;Frost et al, 1993;McFall & Wollersheim, 1979). Consistent with this proposition, empirical research has consistently linked superstitious and magical beliefs to OC symptoms; the strongest relationships demonstrated with compulsive checking (Bolton et al, 2002;Emmelkamp & Aardema, 1999;Frost et al, 1993;Rosen & Tallis, 1995;Roth & Baribeau, 2000;cf.…”
Section: Control-related Beliefs and Ocd 14mentioning
confidence: 99%
“…It may be that once the subjects take some affective distance from the influence of their authoritarian parents, they can consolidate the tendency to criticism that they experienced and internalized with their parents into a useful critical-thinking skill. This possible interpretation can be reinforced by the link found in general between authoritarian parenting and compulsive or perfectionist personality in children (Aycicegi et al, 2002), since both conditions are based on close analytic abilities.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Coppola et al (11) described that the presence of OCS in mothers from a community sample was associated with higher levels of parental stress and the presence of OCS in children. Other studies have shown that dysfunctional parenting, including overprotection and controlling, authoritarian and negative behaviors are more frequent in parents with OCS (12)(13)(14) and that they increase the risk for children to have higher levels of over responsibility, obsessional beliefs related to responsibility and threat estimation, as well as higher rates of psychiatric symptoms, including OCS (15).…”
Section: Introductionmentioning
confidence: 99%